PENGARUH MODEL KOOPERATIF TIPE PAIR CHECK DAN MINAT SISWA TERHADAP HASIL BELAJAR DALAM MATA PELAJARAN AKUNTANSI KELAS X SMKN 1 LUBUK BASUNG - Admiyetti ad; Syamwil Dr (Program Magister Pendidikan Ekonomi (S2), 2015)
The purpose of this research to know is three the influence of learning model and students interest to word the result study in accountancy subjects in grade ten SMKN I Lubuk Basung. The hypothesis of this research three are differences signifikan to word students result study by useed cooperative Type Pair Check model with Numbered Head Together (NHT) at SMKN I Lubuk Basung. Where this research is experiment research. The Population of the research is the ten grade students SMKN I Lubuk Basung. The sampel technique in this research is purposive sampling. Kind of data collection that used is primary data, the last test by using Type Pair Check model and Numbered Head Together, filling up questioner data to word learning interest do it by students. The analysis of this research by technique of Varians analysis (ANOVA) second strip with faktorial desing 2 X 2. The result of this research showed : (1) The students that teach by used Type Pair Check learning model have Bette result study than students teach by Numbered Head Together model (NHT). (2) The students have high interest in study have Better result study than the student low interest in study. (3) There is no interaction between lerning model and student interested to word result study in accountancy students.